Origen y distribucion del genero Zygaena Fabricius, 1775 (Lepidoptera) en la Peninsula Iberica - Fernandez-Rubio, F.
(Es, En)
ilus., 48 ref.
Keywords: ZYGAENIDAE; INSECTA; LEPIDOPTERA; DISTRIBUCION GEOGRAFICA; ESPAÑA